Kontribusi Pelaksanaan Bimbingan Karir Di SMP dan Persepsi Siswa SMP tentang SMK Terhadap Minat Melanjutkan Studi ke SMK - PUSPANELI PUSPANELI (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
This research was conducted based on the low SMP student’s interest in Sungai Penuh City Jambi Province to continue their study to SMK, dispute the government had planned to increase the amount of SMK with comparison SMK: SMA about 70 % : 30 % (Restra Diknas tahun 2007). When the pre research was in progress, there was a fact that SMK was less favorite among SMP students. This research tried to disclose the relation of implementation of career guidance and SMP students perception about SMK has significant relation with the students interest of students to continue their study to SMK. The proposed hypothesis: (1) career guidance implementation had a significant relation with the interest to continue the study to SMK ; (2) SMP students perception about SMK had a sifnificant relation with their interest to continue the study to SMK ; (3) career guidance implementation and SMP students perception about SMK had a sifnificant relation with the students interest to continue study to SMK. This research used correlation method. The research population was students of class IX SMP Sungai Penuh, Jambi. Total populations were 1542 people with the sample 94 people who were taken by stratified proportional random sampling techniques. The data were collected by using questionnaire with likert scale. This research proved that (1) career guidance implementation had a significant contribution about 28,3 %, (2) SMP students perception about SMK had a significant contribution about 17,8 %, (3) both career guidance implementation and SMP students perception about SMK had significant contribution about 39 % to word the interest to continue study to SMK. Based on this research, it could be concluded that career guidance implementation and SMP students perception about SMK were two important factors that contribute the students interest to continue their study to SMK in Sungai Penuh City, Jambi Province. Therefore it is recommented to the related people in SMK to these two factors so that the interest to continue the study to SMK can be increased.